ADSORPTION OF DETERGENT IN WATER USING ACTIVATED CARBON ADSORBENT IN THE FLUIDIZED BED COLUMN - Udyani, Kartika (Jurnal Teknik Kimia, 2010)
This research aims to study the effect of liquid flow rate and bed height on mass transfer coefficient in theadsorption of detergent in water using activated carbon adsorbent in the fluidized bed column. Theexperiment was preceded by an orifice meter calibration and manufacture of detergent solution in water atvarious concentrations. Detergent solution was then fed into the tank inffluen on fluidized bed column andflowed into the column at various flow rates and higt of bed. Effluent from each variation of measuredconcentrations and calculated % detergent absorbed and mass transfer coefficient.The results showed that increasing the flow rate increases the amount of detergent liquid is absorbed andthe mass transfer coefficient. For high-bed 10, 20 and 30 cm, the higher the bed the higher the amount ofdetergent to be absorbed and the mass transfer coefficient. % Detergent which absorbed the highestachieved at influent concentrations of MBAS concentration of 0.054 mg / lt, and 30 cm bed height that isequal to 25.9%. The the highest mass transfer coefficient is 9,457.10-6cm / dt2 on influent concentrationMBAS concentration of 0.054 mg / l and 30 cm bed height.Key word: detergent, activated carbon, % detergent adsorbed, fluidization, mass transfer coeffisien